Sustainability and livestock: a doable combination - Antonella Chiariotti (Revista Científica)
Sustainable development means meeting the needs of the present while ensuring future generations can meet their own needs (European Commission). Rapid urbanization, increased purchasing power, and dietary change drive demand for richer diets and animal-origin proteins, leaving more than 868 million undernourished citizens worldwide and 850 million living in developing countries. Food security could be granted to large populations by reducing food waste, which accounts for 1.3 billion tons per year, or implementing livestock farming and promoting a sustainable food demand. With economic progress and the world’s growing population, estimated to reach more than 9 billion people in 2050, animal proteins will increase as meat and milk demand. Nevertheless, ruminants produce methane, which accounts for most of the agricultural sector emissions (5.8% of the total anthropogenic), raising concerns about their production. If ruminant livestock increase, methane production increases, accelerating global warming inevitably. Depending on resource quality, environmental factors, and social and economic contexts, various types of livestock production systems may vary considerably in sustainability. These livestock systems include extensive grassland, intensive landless, mixed, and family farming systems. Massive worldwide research has investigated the effect of various mitigation strategies. None- theless, the under-representation of certain strategies, geographic regions, the calculation’s robustness, and long-term studies are the main limitations in providing an accurate quantitative estimation of the respective mitigation potential under diverse animal production systems. Ruminant livestock is important not only for producing nutrient-dense meat and milk for human diets but also for providing hides, fiber, manure, and animal power for farming and transportation in many countries and contributing to biodiversity. To obtain this, they eat grass and legume plants that would be inedible to humans or live on land unsuitable for cultivation. Livestock also contributes to muchneeded income for family farmers in developing countries. The buffalo (Bubalus bubalis), represented by a total of 204 million head (3.9 % increase in the last ten years), could play a strategic role due to its peculiar characteristics: the high ability to convert fiber into energy, the longevity, and the adaptation in extreme areas with cold or hot-humid climate where other ruminants cannot thrive. Moreover, it contributes to the sustenance of many people living in rural areas. A multidisciplinary approach considering the environment, animal health and welfare, and social and economic contexts is requested to increase the sustainability of livestock.